“I can’t describe how I could get better, but I would like to” - Conception of health and illness of refugee youth in Germany - van der Meer, Anna Swantje; Durlach, Friederike; Szota, Katharina; Christiansen, Hanna (Frontiers in Psychology, 2023)
Introduction and objective: Almost half of all the people displaced worldwide are children and adolescents. Many refugee children, adolescents, and young adults suffer from psychological stress. However, their utilization of (mental) health services is low, probably due to a lack of knowledge about (mental) health and (mental) health care. The current study aimed to explore concepts of (mental) health and illness of refugee youth as well as assess their mental health literacy (MHL) to arrive at conclusions for improving mental health care access and use. Method: From April 2019 to October 2020, we conducted 24 face-to-face interviews with refugee children and adolescents in an outpatient clinic (n = 8), in youth welfare facilities (n = 10), and at a middle school (n = 6). A semi-structured interview was used to assess knowledge about mental and somatic health and illness as well as corresponding health strategies and care options. The material was evaluated using qualitative content analysis. Results: Participants (N = 24) were between 11 and 21 years old (M = 17.9, SD = 2.4). The coded material was assigned to four thematic main areas: (1) conception of illness, (2) conception of health, (3) knowledge about health care structures in their country of origin, and (4) perceptions of mental health care structures in Germany. Compared to somatic health, the interviewed refugee children and adolescents knew little about mental health. Furthermore, respondents were more aware of opportunities of somatic health promotion, but almost none knew how to promote their mental health. In our group-comparative analysis we observed that younger children possess little knowledge about mental health-related topics. Conclusion: Our results show that refugee youth have more knowledge about somatic health and somatic health care than about mental health (care). Accordingly, interventions to promote the MHL of refugee youth are necessary to improve their utilization of mental health services and to provide adequate mental health care.